2015
DOI: 10.24178/ijrs.2015.1.2.15
|View full text |Cite
|
Sign up to set email alerts
|

Histological, Ultrastructural and Physiological Studies on the Effect of Different Kinds Of Energy Drinks on the Liver Of Wistar Albino Rat

Abstract: Abstract-Three kinds of energy drinks (Power horse, Red bull and Code red) were used to study their histological, ultrastructural and physiological effects on Wistar albino rat liver. Forty male Wistar albino rats were divided into four groups. Group 1 was the control, while Groups 2, 3 and 4 were each orally administered with a type of the energy drinks daily for 4 weeks. After two and four weeks of treatment, five animals from each group were killed and dissected. The liver was removed, cut and fixed quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 12 publications
9
27
0
2
Order By: Relevance
“…It can be reasonably suggested that the lesions were brought about by tissue damage arising from ED-induced oxidative stress. These results are consistent with a previous report on evidence of hepatotoxicity and alterations in liver ultrastructure in rats treated with different types of EDs [22]. In another study, the lesions in liver and kidney tissues were attributed to potential reaction of taurine with some other active ED ingredient such as caffeine [23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It can be reasonably suggested that the lesions were brought about by tissue damage arising from ED-induced oxidative stress. These results are consistent with a previous report on evidence of hepatotoxicity and alterations in liver ultrastructure in rats treated with different types of EDs [22]. In another study, the lesions in liver and kidney tissues were attributed to potential reaction of taurine with some other active ED ingredient such as caffeine [23].…”
Section: Discussionsupporting
confidence: 93%
“…In another study, the lesions in liver and kidney tissues were attributed to potential reaction of taurine with some other active ED ingredient such as caffeine [23]. In addition, Khayyat and his colleagues found that rats treated with EDs had hepatic cytoplasmic vacuolations due to presence of lipid droplets which were attributed to deteriorative changes within hepatocytes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the histology of one female rabbit in this experimental group that died within the first week of the study and male rabbits sacrificed on day 28 showed hepatic abnormalities such as congestion of central veins and balloon degeneration of hepatocytes. Similar hepatic and renal pathologies were reported in rats by many other researchers (Akande and Banjoko, 2011;Khayyat et al, 2012;Khayyat et al, 2014a), lending credence to the fact that injuries caused by RB and other energy drinks cannot solely be explained by increased fluid intake. In the group of rabbits (group 2) that received 11.5 ml of RB, a dose equivalent to half can or 125 ml of energy drink (which contains 46.3 mg taurine and 3.6 mg caffeine), there were no significant biochemical or haematological changes in the male rabbits and no mortality was recorded.…”
Section: Discussionsupporting
confidence: 60%
“…From the findings of this current study and some more recent ones testing different types of energy drink on rats (Khayyat et al, 2012;Chimezie, 2013;Khayyat et al, 2014aKhayyat et al, , 2014b and rabbits (Ebuehi et al, 2011), RB and other energy drinks may be associated with acute reversible hepatic, renal and possibly haematopoietic injury, which may not be totally explained by increased fluid intake or glucose loading in the drink. Furthermore, the histology of one female rabbit in this experimental group that died within the first week of the study and male rabbits sacrificed on day 28 showed hepatic abnormalities such as congestion of central veins and balloon degeneration of hepatocytes.…”
Section: Discussionmentioning
confidence: 92%
“…These organs include testis (Dias et al, 2015), pancreas, fundus of stomach (Ayuob and ElBeshbeishy, 2016), and liver (Khayyat et al, 2012).…”
Section: Discussionmentioning
confidence: 99%